2018
DOI: 10.1080/10717544.2018.1444683
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor efficacy of liposome-encapsulated NVP-BEZ 235 in combination with irreversible electroporation

Abstract: Irreversible electroporation (IRE) is an emerging minimally invasive tumor ablation technique that delivers short pulses of strong electric fields and kills cancer cells by disrupting their cell membranes with the electric pulses. However, clinical studies report that more than 10% of local tumor recurrences occur at the original ablated site. NVP BEZ-235 (BEZ) is a dual PI3K/mTOR inhibitor that has substantial anticancer effects. However, the clinical trials of BEZ was not satisfactory because of its low bioa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 34 publications
1
17
0
Order By: Relevance
“…More recently, studies have shown that mild hyperthermia results from IRE [19,27,[52][53][54]. However, hyperthermia is a desirable treatment characteristic and has been utilized to enhance the efficacy of IRE when combined with chemotherapeutics to prevent recurrence [55][56][57][58][59].…”
Section: Discussionmentioning
confidence: 99%
“…More recently, studies have shown that mild hyperthermia results from IRE [19,27,[52][53][54]. However, hyperthermia is a desirable treatment characteristic and has been utilized to enhance the efficacy of IRE when combined with chemotherapeutics to prevent recurrence [55][56][57][58][59].…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study also used DPPC and DSPE-PEG liposomes encapsulating BEZ. Their combination with IRE showed antiproliferation efficacy on Hep3B xenografts after a single treatment [11].…”
Section: Discussionmentioning
confidence: 99%
“…Our previous in vitro results [11] for electroporation of Hep3B cells suggests that electroporation in the RE range leads to higher cell viability than does IRE. The same results were observed on HN5 cells (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MTT assay was used to determine the cytotoxic effects of nano-systems against cancer or normal cells. 38 Briefly, after 24 hours of culture, the cells were treated with drug-loaded nano-systems and free drugs at certain concentrations for 24 hours. Subsequently, MTT was added to the treated cells for 3 hours, with added DMSO, and then placed in the cells for 15 minutes.…”
Section: Mtt Assay and Combination Index Calculationmentioning
confidence: 99%